Occupational choices and career orientations of students in girls anatolian imam hatip high schools - ÖZDEMİR, ALİ (My University, 2022)
This study aims to determine the factors affecting the occupational choice and career orientation of senior students in Girls Anatolian Imam Hatip High Schools (Religious Vocational High School) and reveal what the students who turn to different occupation groups are affected. The study was conducted using the "phenomenology" pattern, which is one of the qualitative approaches. The research was conducted with 25 students studying in five different Girls Anatolian Imam Hatip High Schools selected from Istanbul in the 2019-2020 academic year. Twenty-five students were selected using "criterion sampling", one of the purposive sampling methods. The data of the study were collected using the "interview" method, and a "semi-structured interview form" was used during the interview. The data were analyzed by the "descriptive analysis" method. This study has been guided by the fact that teachers, families, and policymakers clearly know whether the students in Imam Hatip High Schools, which were established to raise religious officials; make their choices in line with their own interests, abilities, skills, wishes, and desires or are influenced by their environment and that they have made different occupational orientations and preferences in recent years. It was determined that students have found common ground in the lifelong development process besides individual differences in their career and occupational choices. It is seen that students' occupational thoughts, which develop in the form of dreams at an early age, progress from abstract to more realistic and concrete as they grow up and develop; changes and even indecisions occur with the increasing number of effective factors and the predominance of personal desires. It is thought that it will help restructure the studies to be conducted in Turkey since the research is a study to discover "factors affecting the occupational choice and career orientation".
Keywords: Occupational Choice; Career Orientation; Imam Hatip High Schools